Skill and Knowledge Improvement Training on Honey and Propolis Commercialization in Central Bangka Regency - Gemilang Lara Utama; Mahani Mahani; Mohamad Djali (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
The development of honey and propolis as commercial commodities from Central Bangka Regency meet an obstacle considering the technology and marketing target. In order to develop the potential of honey and propolis as commercial products from Central Bangka Regency, identification, technical training and monitoring has been done as the methodology. The results shows identification of Honey and Propolis productivities showed that estimated 19,785 kg / year honey, 3,957 kg / year propolis, with total Kelulut colonies of more than 3957 colonies will resulted. Meanwhile the quality aspect of Kelulut honey found diastase enzyme activity of 1.68 DN, with propolis quality shown polyphenol levels reaching 2587.95 mg / kg with the characteristics that preferred by consumers and industry. Training and monitoring could increase the skill and knowledge of farmer groups